Antiques handbook & price guide 2024-2025 - Miller, Judith, 1951-2023; Wainwright, John (Millers, a division of Mitchell Beazley, 2024)
Miller's Antiques Handbook & Price Guide remains the essential and trusted guide to the antiques market. It has earned the reputation of being the book no dealer, collector or auctioneer should be without. Compiled by the late Judith Miller, world-renowned antiques expert and co-founder of the book, the guide features more than 8,000 antiques. Comprehensive sections cover Ceramics, Asian Antiques, Furniture, Glass, Silver and Metalwares, Jewellery and objets de vertu, Clocks and Watches, Books, Textiles, Toys, Decorative Arts and Modern Classics. Special features explain why one piece is worth more than another, show how to value an item and teach you to be your own valuer. Biographies of designers and factories give the background information you need to help date and value objects, while special 'Judith Picks' sections give fascinating background and valuation details for particularly interesting or unusual objects."--Amazon.